Decreases in Rotavirus Hospitalizations: Impact Data Pre- and 3 Years Post- First Publically Funded Programs. (1st June 2016) - Saux, N Le; Halperin, S; Vaudry, W; Scheifele, D; Bettinger, J
Abstract: BACKGROUND: Since January 2012, almost all Canadian provinces have implemented publically funded rotavirus immunization programs. IMPACT had been doing routine active surveillance for rotavirus hospital-izations at pediatric hospitals in 7 provinces since 2005. OBJECTIVES: Determine changes in hospitalization for rotavirus infection pre and post vacination programs. DESIGN/METHODS: Active, surveillance of patients hospitalized for rotavirus infections was conducted by IMPACT from January 1 2010 to December 2015 at 12 paediatric hospitals. Rotavirus hospitalization data was compared for periods pre (2010-2011) and post (2012-2014) implementation of publically funded immunization programs. Six sites were located in jurisdictions that had publically funded programs as of January 2012. RESULTS: Initiation of rotavirus vaccine programs have resulted in a 43% overall reduction in hospitalizations for rotavirus infection in pediat-ric hospitals in Canada with the greatest decreases seen in provinces with programs that were established as of January 2012 where there was a 66% reduction in hospitalizations. Overall, the average yearly number of hospi-talizations for 2012-2014 was 279, compared to 490 in 2010-2011. Six sites with publically funded programs since 2012 had a yearly average of 121.3 cases identified in 2012-2014 compared to an average of 360 cases in 2010-2011. The average yearly number of hospital acquired cases decreased from 78 to 24.7 in sites with vaccine programs whereas sites without increased (26.5 to 33.7 average cases yearly). The proportion of cases occurring in children <2 years was significantly lower in sites with programs (51.6% vs. 72.5%; p<0.0001). In 2012-2014, 63.4% of children were <2 years compared to the period 2010-2011 where 67.7% were <2 years. The seasonal peak in infections has decreased over time, especially in the age groups 6-11 months and 12 to 24 months. CONCLUSION: Publically funded rotavirus vaccine programs have resulted in important reductions in hospitalizations due to community acquired and hospital acquired rotavirus infections in pediatric hospitals in Canada with the greatest decreases seen in provinces with programs that were established as of January 2012. The proportion of children < 2 years hospitalized with rotavirus infection is decreasing at sites with established programs. Given the >85% efficacy of rotavirus vaccine, increasing uptake and delivery throughout Canada could potentially decrease admissions further.